2019
DOI: 10.1101/812149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lineage-Specific Epigenomic and Genomic Activation of the Oncogene HNF4A Promotes Gastrointestinal Adenocarcinomas

Abstract: AbstractBackgroundsGastrointestinal adenocarcinomas (GIACs) of the tubular GI tract including esophagus, stomach, colon and rectum comprise most GI cancers and share a spectrum of genomic features. However, the unified epigenomic changes specific to GIACs are less well-characterized.We applied mathematical algorithms to large-scale DNA methylome and transcriptome profiles to reconstruct transcription factor (TF) networks using 907 GIAC samples… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 61 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…In contrast to HCC, where an overall diminished HNF4A signaling is observed in most studies, as discussed above, several gastrointestinal adenocarcinomas (GIAC) including esophageal, gastric, pancreatic, and colorectal adenocarcinomas are characterized by increased HNF4A expression [ 181 , 182 ]. This finding was recently confirmed by a large-scale transcriptomic and DNA methylomic study on 907 GIAC samples from The Cancer Genome Atlas [ 153 ]. The latter work furthermore revealed that HNF4A overexpression in GIAC was driven by both genomic and epigenomic mechanisms, as illustrated by the high prevalence of HNF4A gene locus amplification in GIAC and the increased chromatin accessibility of its promoter, respectively.…”
Section: Hnf4 Loss Contributes To Loss Of Identity In Diseasementioning
confidence: 52%
See 3 more Smart Citations
“…In contrast to HCC, where an overall diminished HNF4A signaling is observed in most studies, as discussed above, several gastrointestinal adenocarcinomas (GIAC) including esophageal, gastric, pancreatic, and colorectal adenocarcinomas are characterized by increased HNF4A expression [ 181 , 182 ]. This finding was recently confirmed by a large-scale transcriptomic and DNA methylomic study on 907 GIAC samples from The Cancer Genome Atlas [ 153 ]. The latter work furthermore revealed that HNF4A overexpression in GIAC was driven by both genomic and epigenomic mechanisms, as illustrated by the high prevalence of HNF4A gene locus amplification in GIAC and the increased chromatin accessibility of its promoter, respectively.…”
Section: Hnf4 Loss Contributes To Loss Of Identity In Diseasementioning
confidence: 52%
“…In line with the HNF4A loss observed in chronic liver injuries, a number of studies have reported decreased HNF4A expression in HCC. Indeed, lower HNF4A transcript levels were found in rodent models of hepatocarcinogenesis, as well as in HCC patients [ 151 , 152 , 153 ], although not all studies concur [ 154 ]. Consistent with HNF4A being a liver tumor suppressor, deletion of Hnf4a promotes the occurrence of HCC in mice [ 155 , 156 ].…”
Section: Hnf4 Loss Contributes To Loss Of Identity In Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with substantial involvement of these core TFs in EAC transcriptome, they played positive roles to maintain survival and proliferation of EAC cells. SE-driven LIF, LIFR and HNF4A represented leading candidates for CRC downstream targets which exhibited both disease-specificity and therapeutic venerability [ 71 , 73 ].…”
Section: Strategy and Methodology For Crc Identificationmentioning
confidence: 99%